The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.jhep.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol use is associated with improved survival in patients with liver cirrhosis and ascites

Abstract: The safety of carvedilol and other non-selective beta-blocker drugs in patients with liver cirrhosis and ascites is still debated. In this study, we have shown that carvedilol therapy in these patients was associated with reduced risk of mortality, particularly in those with mild ascites. We concluded that low dose, chronic treatment with carvedilol in patients with liver cirrhosis and ascites is not detrimental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 30 publications
3
73
0
Order By: Relevance
“…This is possibly attributed to the paucity of randomized controlled trials including carvedilol. Recently, a large retrospective study demonstrated a 41% reduction in mortality risk with carvedilol therapy . Therefore, larger prospective trials with carvedilol are needed to elucidate the potential benefits of this drug in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly attributed to the paucity of randomized controlled trials including carvedilol. Recently, a large retrospective study demonstrated a 41% reduction in mortality risk with carvedilol therapy . Therefore, larger prospective trials with carvedilol are needed to elucidate the potential benefits of this drug in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another propensity score–matched retrospective analysis of 264 patients with cirrhosis and ascites showed that carvedilol (median dose, 12.5 mg) was associated with a reduction of mortality risk when compared with patients not on carvedilol. Interestingly, the mortality benefit was no longer significant in patients with moderate or severe ascites, but carvedilol use was not associated with worse outcomes in these groups …”
Section: Use Of Nsbbs In Advanced Cirrhosis: Clinical Evidencementioning
confidence: 93%
“…In contrast with Sersté et al's study, several larger, well‐designed, observational studies of patients with ascites have now demonstrated improved survival with NSBB therapy at modest doses (Table ) . The survival benefit of NSBBs extends to some of the sickest subgroups of patients with cirrhosis.…”
Section: Key Pointsmentioning
confidence: 93%
“…[6][7][8][9] In contrast with Serst e et al's 3 study, several larger, well-designed, observational studies of patients with ascites have now demonstrated improved survival with NSBB therapy at modest doses (Table 1). [5][6][7][8][9][10][11] The survival benefit of NSBBs extends to some of the sickest subgroups of patients with cirrhosis. In a multivariable, propensity risk score-matched competing risk Cox analysis of 322 patients with ascites wait-listed for liver transplantation, use of propranolol (with a median dose of 80 mg/day) or carvedilol (with a median dose of 6.25 mg/day) was associated with a 45% reduction in mortality in the overall cohort and a 65% reduction in mortality in the subgroup of patients with refractory ascites.…”
mentioning
confidence: 99%